Mitochondrial pleomorphy in plant cells is driven by contiguous ER dynamics - Jaipargas, Erica-Ashley; Barton, Kiah A.; Mathur, Neeta; Mathur, Jaideep (Frontiers in Plant Science, 2015)
Mitochondria are pleomorphic, double membrane-bound organelles involved in cellular energetics in all eukaryotes. Mitochondria in animal and yeast cells are typically tubular-reticulate structures and several micro-meters long but in green plants they are predominantly observed as 0.2-1.5µm punctae. While fission and fusion, through the coordinated activity of several conserved proteins, shapes mitochondria, the endoplasmic reticulum (ER) has recently been identified as an additional player in this process in yeast and mammalian cells. The mitochondria-ER relationship in plant cells remains largely uncharacterized. Here, through live-imaging of the entire range of mitochondria pleomorphy we uncover the underlying basis for the predominantly punctate mitochondrial form in plants. We demonstrate that mitochondrial morphology changes in response to light and cytosolic sugar levels in an ER mediated manner. Whereas large ER polygons and low dynamics under dark conditions favor mitochondrial fusion and elongation, small ER polygons result in increased fission and predominantly small mitochondria. Hypoxia also reduces ER dynamics and increases mitochondrial fusion to produce giant mitochondria. By observing elongated mitochondria in normal plants and fission-impaired Arabidopsis nmt1-2 and drp3a mutants we also establish that thin extensions called matrixules and a beads-on-a-string mitochondrial phenotype are direct consequences of mitochondria-ER interactions.